Expansion of the Discretion Concept Reviewed from Legal Anti-Positivism - Annisa Salsabila (Jurnal Ilmiah Kebijakan Hukum, 2022)
The terms of discretion have been determined finitely in Article 24 of Law Number 30 of 2014 concerning Government Administration. However, the requirement "not contrary to the provisions of the legislation" was removed after the issuance of Law Number 11 of 2020 concerning Job Creation. This paper examines 3 (three) circumstances related to discretion. First, how is the concept of discretion viewed from the government administration? Second, how is the concept of discretion viewed from the school of legal anti-positivism? Third, what are the parameters of the validity of discretion based on the legislation? This study used a normative juridical method with a statutory, conceptual, and philosophical approach to analyze the norm and concept of discretion. The results of the study indicate that in the administrative field, discretion may be contrary to the provisions of the legislation if there is stagnation of government and it is intended for the public interest. Such a concept departs from a critique of legal positivism which leads to many subsequent ideologies including utilitarianism, legal realism to CLS. The parameters of the validity of discretion are formal legitimacy consisting of authority and procedures as well as material legitimacy. This research suggests that there is a need for heightening the control mechanism for the issuance of discretion through the superiors of the administration officials concerned.